2014
DOI: 10.1186/1756-3305-7-290
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel Schistosoma japonicum antigens using a targeted protein microarray approach

Abstract: BackgroundNovel vaccine candidates against Schistosoma japonicum are required, and antigens present in the vulnerable larval developmental stage are attractive targets. Post-genomic technologies are now available which can contribute to such antigen discovery.MethodsA schistosome-specific protein microarray was probed using the local antibody response against migrating larvae. Antigens were assessed for their novelty and predicted larval expression and host-exposed features. One antigen was further characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 52 publications
0
28
0
2
Order By: Relevance
“…Our previous work 26 has shown that ASC probes from the skin‐ and lung‐draining LNs of the rat were induced by the passage of migrating schistosome larval stages. In addition, our earlier preliminary protein microarray study detected some possible antigens recognized in the skin and lung immune compartments 27 . We have extended this work and attempted to identify parasite protein antigens that are unique to these important sites of parasite elimination and immune priming.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Our previous work 26 has shown that ASC probes from the skin‐ and lung‐draining LNs of the rat were induced by the passage of migrating schistosome larval stages. In addition, our earlier preliminary protein microarray study detected some possible antigens recognized in the skin and lung immune compartments 27 . We have extended this work and attempted to identify parasite protein antigens that are unique to these important sites of parasite elimination and immune priming.…”
Section: Discussionmentioning
confidence: 95%
“…The time points in TC1 were based on observations that immune resistance in the rat has been shown to be highest between 4 and 8 weeks after re‐infection 19 , 60 . The time points in TC2 were selected to capture the local tissue response after schistosome larval migration through the skin and lung after the first and fourth day post infection, respectively, 19 and after allowing a further 5 days for an optimal LN response 26 , 27 , 63 . The cercarial challenge load for TC1 was determined from previous studies 8 , 19 and from preliminary experiments for TC2; 26 specifically, the higher cercarial challenge for the second infection in TC2 ensured that skin‐ and lung‐draining ASCs were adequately stimulated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations